2008
DOI: 10.4038/jnsfsr.v36i1.139
|View full text |Cite
|
Sign up to set email alerts
|

Complete 2D NMR assignment and antifungal activity of ishwarane isolated from <i>Hortonia</i>, a genus endemic to Sri Lanka

Abstract: The tetracyclic sesquiterpene, ishwarane, was isolated from the leaves of the representative species of the genus Hortonia, H. angustifolia, H. floribunda and H. ovalifolia collected in Sri Lanka. The complete 2D NMR assignments are reported. Ishwarane exhibited antifungal activity against Cladosporium cladosporioides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Thus, in order to complete the structure, the remaining two methyl groups (attached to quaternary carbons) were placed at C-1 and C-5. The resulting structure which fitted the data was concluded to be 1, 5, 12-trimethyltetracyclic [6, 3, 0, 0, 0 3, 4, 8 ] dodecane (1) (Ratnayake et al, 2008b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in order to complete the structure, the remaining two methyl groups (attached to quaternary carbons) were placed at C-1 and C-5. The resulting structure which fitted the data was concluded to be 1, 5, 12-trimethyltetracyclic [6, 3, 0, 0, 0 3, 4, 8 ] dodecane (1) (Ratnayake et al, 2008b).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported the isolation of several biologically active and unique natural products from the three species of genus Hortonia ( Ratnayake et al, 2001;Ratnayake et al, 2008a;Ratnayake et al, 2008b;Ratnayake et al, 2008c;Carr et al, 2012). As part of our continuing research to find biologically active compounds from this plant, we isolated one tetracyclic sesquiterpene.…”
Section: Introductionmentioning
confidence: 99%
“…A study was undertaken to investigate the phytochemistry of all three species, based on the near identity of TLC patterns and the mosquitolarvicidal activity of the leaf extracts of the three species. Previously, the authors have reported the isolation of several new butenolides with mosquitolarvicidal activity from the leaves of all three species (Ratnayake et al, 2001(Ratnayake et al, , 2008a(Ratnayake et al, , 2008b. It was concluded from these studies that the three species were phytochemically very similar.…”
Section: Introductionmentioning
confidence: 94%
“…Ishwarane belonging to sesquiterpenoid class was first isolated from the plants Aristolochia indica and Cembopentalum penduliflorum. It has been isolated from the essential oils of Bixa orellana, Corallocarpus epigaeus and Piper fulvescens [12]. Ishwarane exhibited antifungal activity against C. albicans and C. cladosporioides [12,13].…”
Section: Chemical Compositionmentioning
confidence: 99%